Prospecting the theragnostic potential of the psycho-neuro-endocrinological perturbation of the gut-brain-immune axis for improving cardiovascular diseases outcomes - Rajan, Emilda Judith Ezhil; Alwar, Sai Varsaa; Gulati, Richa; Rajiv, Rohan; Mitra, Tridip; Janardhanan, Rajiv (Frontiers in Molecular Biosciences, 2024)
Deciphering biological derivatives and their effective influence on psychological parameters is an elective notion on the rise for a better understanding of body-mind perspectives in health. Recent evidence suggests a role for the gut-brain immune axis as an attractive theranostic target due to its innate capacity to excite the immune system through activating monocyte exosomes. These exosomes induce spontaneous alterations in the microRNAs within the brain endothelial cells, resulting in an acute inflammatory response with physiological and psychological sequelae, evidenced as anxiety and depression. Exploring the role of the stress models that influence anxiety and depression may reflect on the effect and role of exosomes, shedding light on various physiological responses that explain contributing factors for cardiovascular disorders. The pathophysiological effects of gutmicrobiome dysbiosis are further accentuated by the alterations in the glucose metabolism leading to Type 2 Diabetes, which is known to be a risk factor for cardiovascular disorders (CVDs). Understanding the role of exosomes and their implications on cell-to-cell communication, inflammatory responses, and neuronal stress reactions, can easily lend insight into the gut-brain immune axis and downstream cardiovascular sequelae.